Sonodynamic Effects of a Novel Ether-Group Modified Porphyrin Derivative Combined With Pulsed Low-Intensity Ultrasound on PC-9 Cells - Yinghua Jin; Qi Zhou; Jianxiong Geng; Qingwei Meng; Zixin Wei; Meijuan Ding; Jing Zhou; Yuan Zeng; Wenwu Cao; Wenwu Cao; Fang Liu; Yan Yu (Frontiers Media S.A., 2021)
Sonodynamic therapy (SDT) is a developing modality for cancer treatment based on the synergistic effect of ultrasound and chemical compounds which are known as sonosensitizers. The development of more efficient sonosensitizers has become an urgent issue in this field. In this study, a novel porphyrin derivative (BBTPP) mediated SDT was evaluated on PC-9 cells. Pulsed low-intensity ultrasound (PLIU) was used for its little thermal and mechanical damage. The accumulation of drugs in cells was evaluated through porphyrin fluorescence, and the cytotoxicity of BBTPP was evaluated using a cell counting kit-8 assay. The sonodynamic effect was investigated by Hoechst 33342/PI and Annexin V-FITC/PI double staining, which showed an apoptotic rate of 18.87% in the BBTPP-SDT group, as compared with 1.71%, 1.4%, 1.57%, 3.61%, 11.18% in the control, BBTPP, hematoporphyrin monomethyl ether (HMME), ultrasound, and HMME-SDT groups, respectively. The sono-toxic effect of BBTPP was significantly superior to HMME. Our results showed that BBTPP-SDT resulted in much higher intracellular reactive oxygen species (ROS) and lipid peroxidation levels which were evaluated by 2',7'-dichlorodihydrofluorescein diacetate (H2DCFDA) and Liperfluo assay, respectively. The expressions of Bax, Bcl-2, caspase-9, caspase-8, and cleaved caspase-3 proteins were evaluated to investigate the apoptotic mechanism of BBTPP-SDT. The results of this study showed that the combination of BBTPP and PLIU induced the generation of ROS, resulting in lipid peroxidation, and activated both the extrinsic and intrinsic apoptotic pathways of PC-9 cells. Our results also suggested that the ether group introduced in the side chain of porphyrin could enhance the sono-toxicity of porphyrin-based sensitizers under the sonication of PLIU. These results supported the possibility of BBTPP as a promising sonosensitizer, and an appropriate side chain could enhance the sono-sensitivity of porphyrins.